The Light-to-heat Conversion of Gold Nanoshells and Nanorods in Tissues - Duong, Vu Thuy; Thuong, Trinh Thi; Lien, Nghiem Thi Ha; Hoa, Do Quang; Nhung, Tran Hong (Communications in Physics, 2016)
We perform a set of experiments on photo-heating in tissues containing gold nanoshells (NSs) and nanorods (NRs). The temperature of tissues were measured with different amounts gold NSs and NRs under illumination of a continuous diode laser at 808 nm and power density from 20 to 62 W/cm\(^{2}\). The temperature of the tissues injected gold nanoparticles increased to $66 ± 4\(^{°}\)C for \(2.1 × 10^{8}\) NSs and \(73± 4\) \(^{°}\)C for gold \(5.4 × 10^{9}\) NRs after 10 min exposition at power density 35 W/cm\(^{2}\). The control tissue without gold nanoparticles demonstrated a significantly lower temperature \(40 ± 4\) \(^{°}\)C in the same time of illumination. The temperature can be reached up to around 100\(^{°}\)C for tissue with both NSs and NRs at 62 W/cm\(^{2}\) inrradiation for \(7-10\) min.